2019
DOI: 10.1101/517854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Capturing the Diversity of Subsurface Microbiota – Choice of Carbon Source for Microcosm Enrichment and Isolation of Groundwater Bacteria

Abstract: 22Armatimonadetes) that are poorly represented in published culture collections were 46 abundantly enriched. Further isolation of pure bacterial strains from complex C-amended 47 enrichments led to 51 species representing 4 phyla, 13 orders. Furthermore, 5 isolates 48 with low similarities to published strains were considered to be novel. Results from this 49 study will aid in the design of better cultivation and isolation strategy for maximize the 50 diversity of organisms recovered from subsurface environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Inference of organismal behaviour based on short 16S rRNA gene sequences needs to be taken cautiously owing to the low resolution of the technique to assign taxonomy at the species level, and to the existence of pathogenic traits that may often result from horizontal gene transfer events (Borges et al, 2021). Bearing these caveats in mind, from the six OTUs displaying significantly lower abundance means in treated vs. control larvae, five were assigned to bacterial families/genera ( Xanthomonadaceae/Stenotrophomonas ; Enterobacteraceae/Klebsiella ; Pseudomonadaceae/Pseudomonas ) known to contain typical opportunistic species (see below), while one OTU (OTU376, Chitinophagaceae/Sediminibacterium ) represents a canonical marine/brackish water taxon recognized for its ability to use both simple and complex carbon sources and, consequently, for its role in carbon cycling and secondary production (Wu et al, 2019). At present, it is not possible to anticipate which consequences the depletion of OTU376 in YSA‐treated larvae would have to host–microbiome functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Inference of organismal behaviour based on short 16S rRNA gene sequences needs to be taken cautiously owing to the low resolution of the technique to assign taxonomy at the species level, and to the existence of pathogenic traits that may often result from horizontal gene transfer events (Borges et al, 2021). Bearing these caveats in mind, from the six OTUs displaying significantly lower abundance means in treated vs. control larvae, five were assigned to bacterial families/genera ( Xanthomonadaceae/Stenotrophomonas ; Enterobacteraceae/Klebsiella ; Pseudomonadaceae/Pseudomonas ) known to contain typical opportunistic species (see below), while one OTU (OTU376, Chitinophagaceae/Sediminibacterium ) represents a canonical marine/brackish water taxon recognized for its ability to use both simple and complex carbon sources and, consequently, for its role in carbon cycling and secondary production (Wu et al, 2019). At present, it is not possible to anticipate which consequences the depletion of OTU376 in YSA‐treated larvae would have to host–microbiome functioning.…”
Section: Discussionmentioning
confidence: 99%
“…To link processes and factors from the gene scale to the ecosystem scale, ENIGMA has multiple studies at the field scale ( Step 2a ), mesocosm scale ( Step 2b ), and molecular/species level ( Step 2c ). To facilitate these studies, ENIGMA has major research thrusts aimed at field surveys ( Smith et al, 2015 ; Paradis et al, 2018 ; Zelaya et al, 2019 ; Moon et al, 2020 ); laboratory and bioreactor studies of isolates ( Vaccaro et al, 2016 ; Price et al, 2018 ; Carlson et al, 2019 ; Thorgersen et al, 2019 ); syncoms, enrichments, and improved isolation methods ( Wu et al, 2018 , 2019 ); genetic tool development ( Liu et al, 2018 ; Price et al, 2018 ; Mutalik et al, 2019 ); and bioinformatics analyses and tools ( Price and Arkin, 2019 ; Lui et al, 2020 ; Price et al, 2020 ).…”
Section: Approach To Applying the Framework For Integrated Conceptuamentioning
confidence: 99%
“…ENIGMA has isolated thousands of bacterial and archaeal strains from the ORR site and is exploring the impact of biogeochemistry at field-relevant levels on the survival and function of these isolates ( Wu et al, 2018 ; Carlson et al, 2019 ; Thorgersen et al, 2019 ; Wu et al, 2019 ) ( Step 2c.1 ). At the isolate and molecular levels, we have found that major selective pressures also include concentration, heavy metals, nitrate, and low pH, which alter DNR microbial growth ( Carlson et al, 2019 ; Thorgersen et al, 2019 ).…”
Section: Approach To Applying the Framework For Integrated Conceptuamentioning
confidence: 99%